Un Musée : des chefs-d'oeuvre : Le Musée d'Art Moderne de Liège au Centre Culturel Wallonie Bruxelles. - Bertrand, Pierre; Close, Edouard; De Lulle, Francis; Spehl-Robeyns, M. M.; Centre Culturel Wallonie-Bruxelles, Paris; Ville de Liège (Liège : Museé d'Art Moderne Liège, 1983)
Arp, Hans (Jean) ; Boudin, Eugène ; Chagall, Marc ; Corot, Jean-Baptiste Camille ; Delvaux, Paul ; Derain, André ; van Dongen, Kees ; Dufy, Raoul ; Dunoyer de Segonzac, André ; Ensor, James ; Friesz, Othon ; Gauguin, Paul ; Gromaire, Marcel ; Jeanneret, Charles-Edouard ; Khnopff, Fernand ; Kokoschka, Oskar ; Laurencin, Marie ; Leger, Fernand ; Magnelli, Alberto ; Magritte, René ; Marquet, Albert ; Matisse, Henri ; Monet, Claude ; Pascin, Jules ; Picasso, Pablo ; Pissarro, Camille ; Sérusier, Paul ; Sidaner, Henri-Eugène-Augustin Le ; Signac, Paul ; Stevens, Alfred ; de Toulouse-Lautrec, Henri ; Utrillo, Maurice ; Villon, Jacques ; de Vlaminck, Maurice ; Wouters, Rik
biografie
Un Musée : des chefs-d'oeuvre : Le Musée d'Art Moderne de Liège au Centre Culturel Wallonie Bruxelles, Paris, du 23 septembre 1983 au 8 janvier 1984
Frans
boek